2011
DOI: 10.1007/s11999-010-1661-5
|View full text |Cite
|
Sign up to set email alerts
|

Greater Strength Increase with Cyst Decompression and SLAP Repair than SLAP Repair Alone

Abstract: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…5 Thus, the Lartajet procedure is a viable option for arthroscopic repair failure, in bipolar lesions and when there is a high probability of recurrence. 6 The results of open procedures are higher when compared with the arthroscopic ones in high-risk sports athletes 7 ; however, few studies show bone block results related to athletic activity, in this case, soccer. The objective of this study was to assess professional soccer players treated by the Lartajet technique, analyzing the rate and time of return to sports activities, complications or failures.…”
Section: Introductionmentioning
confidence: 99%
“…5 Thus, the Lartajet procedure is a viable option for arthroscopic repair failure, in bipolar lesions and when there is a high probability of recurrence. 6 The results of open procedures are higher when compared with the arthroscopic ones in high-risk sports athletes 7 ; however, few studies show bone block results related to athletic activity, in this case, soccer. The objective of this study was to assess professional soccer players treated by the Lartajet technique, analyzing the rate and time of return to sports activities, complications or failures.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Other authors have shown that decompression aids in faster recovery of neuropathy, with more rapid increases in strength. 10 A subacromial space approach has been described for SSN decompression but requires a significant resection of the subacromial bursa and places the SSN and coracoclavicular ligaments at risk of iatrogenic injury. 11 …”
Section: Discussionmentioning
confidence: 99%
“…Most authors agree that arthroscopic intra-articular cyst decompression with labral repair is effective and has good clinical outcomes and have reported a high recurrence rate if the labral tear is not repaired, which indicates a strong association of the cyst with SLAP lesion. 4 , 6 , 7 , 10 , 11 Another reported approach to decompress the cyst is through the subacromial space when the cyst is extending superiorly. 12 However, this technique requires thorough bursectomy and has the possible risk of injury to the SSN or coracoclavicular ligament by aggressive soft tissue dissection and also has the possibility of failure to diagnose a concomitant labral tear.…”
Section: Discussionmentioning
confidence: 99%